A young person’s perspective of administrative data research - Romeo, Rianna; Kashef, Shayda (International Journal of Population Data Science, 2025)
Recent public attitudinal studies have shown that the public want to know of the benefits of administrative data research. However, a common challenge is translating this information in an engaging and meaningful way. To bridge this gap, ADR UK hosted a summer intern to translate some research for the public. Drawing from her own perspectives and skill, the intern will create a bespoke translation of administrative data research and accompanying communications campaign over the course of 12 weeks. The intern will work closely with relevant ADR UK researchers and gain feedback from a public panel to ensure the translation is both accurate and engaging. The publication will be available in early September 2025. It will not only add to a suite of publicly-accessible outputs demonstrating the value of administrative data research, but the internship will demonstrate an example of how to meaningfully include young people in administrative data research. The publication and accompanying communications campaign will launch later this year.